The Effect of Fetuin-A and Palmitate on the Translocation of Glucose Transporter-4 Through the Activation of Toll-Like Receptor 4 in Skeletal Muscle Cells - Soebagijo Adi Soelistijo (Journal of Global Pharma Technology, 2020)
Background: Fetuin-A (FetA) is a 63 kD phosphorylated glycoprotein that relates to insulin resistance inhibits autophosphorylation and the activity of insulin receptor tyrosine kinase (IR-TK) at the receptor levels. FetA positively correlates with insulin levels, and homeostasis model of insulin resistance (HOMA-IR). However, the phenomenon is obtained from several studies; a decrease did not always follow the increase of FetA in glucose uptake in the tissue. Aim: To determine the impact of Fetuin-A and Palmitate on TLR4 mediated Glucose Transporter-4 translocation inhibition in normal glucose-tolerance human skeletal muscle cell (h-SkMC). Method: Normal h-SkMC culture were randomly divided into five arms and treated with human- insulin, and deoxy-glucose (GI arm), or human-insulin, deoxy-glucose, and FetuinA (GIF arm), or human-insulin, deoxy-glucose and Palmitate (GIP arm), or human-insulin, deoxyglucose, FetuinA and Palmitate (GIFP arm). The control arm was without any treatment. The effects of insulin, glucose, FetuinA, and Palmitate on the expression of TLR4, Akt, GLUT-4 were evaluated by immunofluorescence microscopy. The expression of TNF- and IL-6 were measured by ELISA assay, and glucose uptake was measured by spectrophotometry assay. The results were obtained and subject to comparative test and pathway analysis. Results: The treatment with glucose+insulin (GI), FetA (GIF), Palmitate (GIP), and Palmitate+FetA (GIFP) increased TLR4 expression significantly compared to control arm (p<0.05) and only treatment with GI and GIF significantly increased the expression of GLUT-4 compared to control arm (p<0.05). All treatment arms and control arms were not significantly different in altering glucose transport. The treatment with Palmitate significantly decreased GLUT-4 expression and independence of TLR4 expression. Conclusion: The treatment with FetA alone or in combination with Palmitate in normal h-SkMC significantly increases the expression of TLR4 but does not alter GLUT-4 translocation and glucose transport. These results provide novel evidence indicating that acute exposure of FetuinA and Palmitate on normal glucose-tolerance h-SkMC does not induce insulin resistance.Keywords: FetA, Palmitate, TLR4, GLUT-4, TNFα, IL-6, Glucose transport.